1989
DOI: 10.1017/s0022029900026431
|View full text |Cite
|
Sign up to set email alerts
|

Low resolution NMR spectroscopy: a tool to study protein denaturation: I. Application to diamagnetic whey proteins

Abstract: SUMMARY. A method using low resolution NMR spectroscopy is described for investigating whey protein thermal denaturation. The method is based on measuring at 20 °C changes in water proton transverse (T 2 ) relaxation parameter following the denaturing treatment. This parameter is shown to be sensitive to protein denaturation and not to other phenomena such as gelation. Examples are given for the qualitative study of protein thermal denaturation in whey protein concentrate, /Mactoglobulin, a-lactalbumin, bovine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 27 publications
5
32
1
Order By: Relevance
“…This has already been reported for most of the protein-water systems studied (Oakes, 1976a,b;Lelihvre and Creamer, 1978;Mahdi, 1979;Richardson et al, 1986;Lambelet et al, 1989;Myers-Betts and Baianu, 1990a) and is consistent with a fast exchange between bound and free water populations (Derbyshire, 1982).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This has already been reported for most of the protein-water systems studied (Oakes, 1976a,b;Lelihvre and Creamer, 1978;Mahdi, 1979;Richardson et al, 1986;Lambelet et al, 1989;Myers-Betts and Baianu, 1990a) and is consistent with a fast exchange between bound and free water populations (Derbyshire, 1982).…”
Section: Resultssupporting
confidence: 80%
“…The variation in transverse relaxation rates observed during heating conalbumin solution can therefore be associated with changes in the conformation of the protein. An increase in transverse relaxation rates has already been observed following thermal treatments of various proteins such as whey and egg white proteins (Oakes, 197613;Lambelet et al, 1988Lambelet et al, , 1989. In the case of bovine serum albumin (BSA), it was shown that on thermal denaturation the protein proton transverse relaxation rates become much higher, but the longitudinal relaxation rates remain unchanged (Oakes, 1976b).…”
Section: Protein C O N C E N T R a T I O N (W/w)mentioning
confidence: 99%
See 2 more Smart Citations
“…The increased water proton relaxation rate induced by aggregation could be explained by the simple molecular processes of diffusion and chemical exchange (Hills et al (27,28) and Lambelet et al (38)). The main effect of aggregation is to reduce the protein proton transverse relaxation time because the dipole-dipole interactions between the protein protons are no longer as efficiently averaged by rotational motion.…”
Section: Resultsmentioning
confidence: 99%